Frailty is associated with impaired cerebral oxygenation recovery during. (14th October 2021) - Perez-Denia, L; Claffey, P; Delgado-Ortet, M; Byrne, L; Kenny, R A; Finucane, C
Abstract:  : Frailty is associated with impaired peripheral circulatory responses to standing in older adults. However, little is known about how frailty affects cerebrovascular function during such activities of daily living. Here we investigate the association between frailty and cerebral oxygenation during standing in a large clinical cohort of fallers and fainters. Participants were recruited from a national Falls and Syncope unit and underwent an active stand test (5–10 minutes lying supine, 3 minutes standing) with concurrent monitoring of continuous blood pressure (BP) and heart rate (HR) and tissue saturation index (TSI) using near-infrared spectroscopy (NIRS). Frailty was measured using a count of deficits (27 morbidities). Robust linear regression was applied to study the association between features of dynamic cerebral oxygenation (changes from baseline at nadir, overshoot, 30s and steady state; and recovery rate) and frailty while correcting for covariates. A p-value <0.05 was considered significant. Frailty was associated with deficits in TSI at 30s after standing (β: −0.165, CI: (−0.261, −0.069), p=0.005), as well as a lower diastolic BP at 30s (β: −1.346, CI: (−2.287, −0.405), p=0.032) and standing steady-state (β: −1.182, CI: (−2.038, −0.325), p=0.032). When stratified by gender, frailty was associated in women with a lower TSI at overshoot (β: −0.174, CI: (−0.312, −0.037), p=0.043) and 30s (β: −0.216 (−0.344, −0.089), p=0.010), and impaired DBP recovery at overshoot (β: −1.623, CI: (−2.865, −0.391), p=0.045) and attenuated HR response at 30s (β: −0.701, CI: (−1.246, −0.155), p=0.036). No associations were found in men. Impaired cerebral oxygenation and BP responses to standing are associated with frailty in patients with falls and syncope, with stronger effects in women, suggesting that frailty may increase risk of hypoperfusion and consequent syncope, falls, and brain ageing. Our results demonstrate the clinical utility and feasibility of using NIRS in this context which can be used to further personalise patient management. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Irish Research Council